German for Hospitality: An Analysis of the Structure, Content and Language Level of Text Book Used at Bali Tourism Polytechnic - Hartanti Woro Susianti; I Nyoman Sudiana; Ida Bagus Putrayasa; Ni Made Rai Wisudariani (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2025)
This article presents a comprehensive analysis of the textbook Zimmer Frei: Deutsch im Hotel within the context of German language instruction for hospitality studies at the Bali Tourism Polytechnic. The analysis includes an evaluation of the textbook’s structure, content quality, and language level based on the framework provided by Rösler and Würffel (2014) and relevant competency standards. The findings indicate that the textbook is well-suited for training essential communication skills in hospitality services, such as guest reception, reservations, and complaint handling, although adjustments are needed concerning the allocation of instructional time and students’ German proficiency levels. The textbook is also considered effective in supporting context- and situation-based learning but requires updates to the audio learning media for greater accessibility. This article aims to provide recommendations for the development of effective teaching materials that enhance German language programs in the hospitality field.